2018
DOI: 10.1016/j.cirp.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Value creation in production: Reconsideration from interdisciplinary approaches

Abstract: This paper presents reconsideration of value creation in production from various aspects of value viewpoints in several disciplines such as production engineering, social sciences, and human sciences. The focal point of investigations is value co-creation by the provision of products and services in and for society. In the past, some methods of social sciences and others proved to be useful in making production more efficient. At present, such methods must help to realise value creation. In fact, production mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 111 publications
1
13
0
Order By: Relevance
“…The research found dynamic capabilities and market attractiveness affect cocreation strategy and collaboration strategy, as well as having an impact on the value creations of SMEs. This is in line with previous research in dynamic capabilities of SMEs and value creation in production by Damaskopoulos,Gatautis, & Vitkauskaitė (2008) and Kaihara, Nishino, Ueda, Tseng, Váncza, Schönsleben, & Takenaka, (2018). Dentoni, D., Bitzer, V., & Pascucci, S. (2016) also studied co-creation and dynamic capabilities, where a firm can co-create their dynamic capabilities by engage with their stakeholders.…”
Section: Resultssupporting
confidence: 86%
“…The research found dynamic capabilities and market attractiveness affect cocreation strategy and collaboration strategy, as well as having an impact on the value creations of SMEs. This is in line with previous research in dynamic capabilities of SMEs and value creation in production by Damaskopoulos,Gatautis, & Vitkauskaitė (2008) and Kaihara, Nishino, Ueda, Tseng, Váncza, Schönsleben, & Takenaka, (2018). Dentoni, D., Bitzer, V., & Pascucci, S. (2016) also studied co-creation and dynamic capabilities, where a firm can co-create their dynamic capabilities by engage with their stakeholders.…”
Section: Resultssupporting
confidence: 86%
“…SDL also emphasises the notion of value co-creation, which refers to the processes or activities that underlie mutual resource integration and that incorporate different actor roles into the principle context. In engineering research, innovation has been discussed as seeking a way to create sustainable value (Kaihara et al, 2018;Ueda et al, 2009). A service is expected to be a new possibility to solve sustainability issues.…”
Section: Research Scope Challenge and Approach 21 Innovation As A Co-creative Activity And Research Scopementioning
confidence: 99%
“…The growth and sustainability of European economy requires a change from competition based on cost reduction towards high value added activities by adopting a competitive sustainable manufacturing (CSM) paradigm [12]. Indeed, European countries need continuous innovation to keep their position in a global market place while creating value in a sustainable society [13,14]. The development of the sustainability paradigm has translated over the years into a series of global initiatives with broad objectives but without precise quantitative targets.…”
Section: Missions For Manufacturing Industrymentioning
confidence: 99%